Schaum's outline of theory and problems of Data Structures with C++ - Hubbard, John R.; Hubbard, John R. (New Delhi, TMH, 2000)
Over 119,000 computer science majors and advanced placement students enroll yearly in required Data Structures/Computer Science II classes, and C++ is the language they use. Adhering to the new ISO standard for C++ (which has rendered previous C++ guides obsolete) Schaums presents the most up-to-date study guide on Data Structures, simplifying and demonstrating difficult concepts through solved problems and examples.
Appendices A-E 268-386p.; Index 399-407p.
Keywords: C programming; Computer Science; Data Structure; General Science